The Effect of Discovery Learning Model Using Canva and I-Spring Suite on Student Learning Outcomes and Motivation in Stoichiometry Material - Yohana Fransiska Sitanggang; Ratna Sari Dewi (Universitas Islam Negeri Alauddin Makassar, 2025)
The aim of this research is to determine whether there is an influence and correlation between the Discovery Learning model using Canva and I-Spring Suite on learning outcomes and student motivation in stoichiometry material. This research uses a quasi-experiment with a quantitative approach. The analysis technique used is the two-party t test. From the results of data analysis on learning outcomes and student motivation, it was found that there was an influence of the Discovery Learning model using Canva and I-Spring suite on student learning outcomes and motivation on stoichiometry material. Based on the data obtained, namely tcount>ttable on student learning outcomes (2.93>1.66), and on student motivation (2.48>1.66). Based on the data, it is known that there is an increase in learning outcomes in each class when implementing learning models and media (67.15% and 63.5%). In terms of student motivation, it can be seen that the percentage of student motivation is 74.4% for experimental class I and 71.3% for experimental class II. The correlation of increasing learning outcomes and student motivation in experimental class I and experimental class II is quite low, namely 0.0116 and 0.0114.